Order flow, dealer profitability, and price formation - Locke, Peter; Onayev, Zhan (Journal of Financial Economics, 2007)
We analyze the dynamics of the S&P 500 futures price, finding both short- and long-run effects of order flow on price. While price moves strongly with the order flow in the short-run, the long-run impact is slightly negative, attributable to costly slippage from a hedging propensity in futures markets. We find strong evidence of a state dependence in the relation between price and order flow, using both volume and floor trader income measures as states. We also find that both the long- and short-run impacts of order flow are greater when dealer income is higher.